2017
DOI: 10.1002/adhm.201700073
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve Cancer Photothermal Therapy Mediated by Nanomaterials

Abstract: The deployment of hyperthermia-based treatments for cancer therapy has captured the attention of different researchers worldwide. In particular, the application of light-responsive nanomaterials to mediate hyperthermia has revealed promising results in several pre-clinical assays. Unlike conventional therapies, these nanostructures can display a preferential tumor accumulation and thus mediate, upon irradiation with near-infrared light, a selective hyperthermic effect with temporal resolution. Different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
173
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 221 publications
(174 citation statements)
references
References 172 publications
(198 reference statements)
1
173
0
Order By: Relevance
“…At present, because of the unique superiorities of high specificity as well as minimal invasiveness, photothermal therapy (PTT) has become a promising strategy in treating cancer superior to chemotherapy to some extent . Recently, near‐infrared (NIR) fluorescent dye, like IR820 has also attracted tremendous interest in phototherapy due to their strong photonic absorbance in NIR wavelength range (700–900 nm) and high ability to convert the absorbed NIR optical energy into thermo energy, which can be justified by that the temperature of tissue reaches 55–95 °C within a few minutes when exposed to NIR in the presence of NIR agent . Moreover, most NIR dyes are nontoxic .…”
Section: Introductionmentioning
confidence: 99%
“…At present, because of the unique superiorities of high specificity as well as minimal invasiveness, photothermal therapy (PTT) has become a promising strategy in treating cancer superior to chemotherapy to some extent . Recently, near‐infrared (NIR) fluorescent dye, like IR820 has also attracted tremendous interest in phototherapy due to their strong photonic absorbance in NIR wavelength range (700–900 nm) and high ability to convert the absorbed NIR optical energy into thermo energy, which can be justified by that the temperature of tissue reaches 55–95 °C within a few minutes when exposed to NIR in the presence of NIR agent . Moreover, most NIR dyes are nontoxic .…”
Section: Introductionmentioning
confidence: 99%
“…Many of the aforementioned techniques have being tested in vivo, revealing promising results and a low toxicity profile. However, despite all these efforts, only a few designs have reached pre-clinical trials, and their true therapeutic capability is yet to be revealed [1]. In summary, this promising therapy, despite its potential and very many applications in health, still requires a great deal of fundamental research to address certain issues that are still not fully understood.…”
Section: Introduction : H Y P E R T H E R M I a Nowadaysmentioning
confidence: 99%
“…Among all those materials used, by far the most popular is gold, thanks to its straightforward synthesis, ease of functionalization, optical properties and low toxicity [3,5]. Carbon-based nanomaterials also represent a strong branch of research thanks to its structural versatility, allowing to create configurations with unique optical properties such as carbon nanotubes and nanographene oxide [1], among others [5]. In addition, there have been many attempts of alternative approaches by combining PTT with other techniques like drug delivery [3,6,7], photodynamic therapy [3,8], optoacoustic imaging [9,10] and immunotherapy [11] among others.…”
Section: Introduction : H Y P E R T H E R M I a Nowadaysmentioning
confidence: 99%
See 2 more Smart Citations